2015
DOI: 10.1039/c4ra14887h
|View full text |Cite
|
Sign up to set email alerts
|

Paper imbibition for timing of multi-step liquid handling protocols on event-triggered centrifugal microfluidic lab-on-a-disc platforms

Abstract: Imbibition of liquid along a paper strip offers enhanced flow control of dissolvable film valve on the centrifugal platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…Event-triggered valving circumvents this restriction [6][7]. Here, the arrival of liquid at defined locations on the disc coordinates a sequential opening of valves; valve actuation is thus decoupled from changes in the spin rate and support instrumentation.…”
Section: Digital Flow Control Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Event-triggered valving circumvents this restriction [6][7]. Here, the arrival of liquid at defined locations on the disc coordinates a sequential opening of valves; valve actuation is thus decoupled from changes in the spin rate and support instrumentation.…”
Section: Digital Flow Control Schemesmentioning
confidence: 99%
“…Based on the recently introduced, event-triggered flow control scheme [6,7], highly functional microfluidic circuits can be assembled in a modular fashion from a limited set of LUOs to implement a broad repertoire of multi-step, multi-reagent bioassay protocols in a sample-toanswer fashion. Furthermore, it has been demonstrated that the chips could be progressively miniaturized to significantly enhance integration density (i.e., the number of assay steps and/ or tests per disc) and thus boost the overall cost efficiency and functionality of the LoaD platform.…”
Section: Introductionmentioning
confidence: 99%
“…Nwankire et al 17,18 built on this system by integrating and automating multistep bioassay protocols actuated by the dissolvable-film-based centrifugopneumatic valving scheme. Kinahan et al advanced this sacrificial technology to an event-triggered valving paradigm that enables the more dynamic control of fluids on a centrifugal microfluidic platform 19,20 . Dimov et al 21 combined a hydrophobic membrane and dissolvable film to improve on-disc solid-phase purification of nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…While it is hard to make a general statement, active mixers tend to significantly accelerate mixing; however, they are typically more complicated to fabricate and integrate, and more complex to control.Passive mixers use the hydrodynamic energy, e.g., provided by a pressure difference created by a pump, gravity or centrifugal force, to restructure the liquid flows in such ways that fast mixing is promoted. Examples for passive mixing principles are bas/relief structures incorporated in the channel walls to induce advection in a liquid flow [63] and multi-lamination of flow [64], e.g., through split-and-recombine strategies [65,66].Mixing principles using the specific effects on centrifugal lab-on-a-disc platforms [67] include Coriolis-force induced split-and-recombine [68], advection [69], reciprocating flow induced by centrifugo-pneumatic pumping [52,70], mixing enhanced by the Euler force through periodically changing angular acceleration [71,72] and/or magnetic beads [51], mixing by use of chemically generated bubbles [73], and mixing enhanced by deformation of soft chamber walls [74,75]. Mixing can also be enhanced through external pumping such as provision of external air sources [76,77].…”
mentioning
confidence: 99%
“…Mixing principles using the specific effects on centrifugal lab-on-a-disc platforms [67] include Coriolis-force induced split-and-recombine [68], advection [69], reciprocating flow induced by centrifugo-pneumatic pumping [52,70], mixing enhanced by the Euler force through periodically changing angular acceleration [71,72] and/or magnetic beads [51], mixing by use of chemically generated bubbles [73], and mixing enhanced by deformation of soft chamber walls [74,75]. Mixing can also be enhanced through external pumping such as provision of external air sources [76,77].…”
mentioning
confidence: 99%